2016
DOI: 10.1534/g3.116.033308
|View full text |Cite
|
Sign up to set email alerts
|

Genomic, Transcriptomic, and Proteomic Analysis Provide Insights Into the Cold Adaptation Mechanism of the Obligate Psychrophilic Fungus Mrakia psychrophila

Abstract: Mrakia psychrophila is an obligate psychrophilic fungus. The cold adaptation mechanism of psychrophilic fungi remains unknown. Comparative genomics analysis indicated that M. psychrophila had a specific codon usage preference, especially for codons of Gly and Arg and its major facilitator superfamily (MFS) transporter gene family was expanded. Transcriptomic analysis revealed that genes involved in ribosome and energy metabolism were upregulated at 4°, while genes involved in unfolded protein binding, protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 74 publications
3
52
0
Order By: Relevance
“…The first integrated study on the genomic, transcriptomic and proteomic perspectives of M. psychrophila provided insights into the cold adaptation mechanism of psychrophilic fungi (Su et al 2016). The comparative genomic analysis with that of other psychrophilic, thermophilic and mesophilic fungi indicated that M. psychrophila had a specific codon usage preference, especially for codons of Gly and Arg and its major facilitator superfamily transporter gene family was expanded.…”
Section: Representative Cold-adapted Fungal Speciesmentioning
confidence: 99%
“…The first integrated study on the genomic, transcriptomic and proteomic perspectives of M. psychrophila provided insights into the cold adaptation mechanism of psychrophilic fungi (Su et al 2016). The comparative genomic analysis with that of other psychrophilic, thermophilic and mesophilic fungi indicated that M. psychrophila had a specific codon usage preference, especially for codons of Gly and Arg and its major facilitator superfamily transporter gene family was expanded.…”
Section: Representative Cold-adapted Fungal Speciesmentioning
confidence: 99%
“…These microbes have acquired several strategies against freezing that inevitably accompany ice crystal formation and overcome physical damages. An example of such a strategy is the production of cryoprotective substances, such as glycerol , trehalose , and ice‐binding proteins (IBPs) , which inhibit ice crystal growth. Nevertheless, cold‐survival mechanism and phylogenetic relationship of microbial IBPs, especially in fungi, are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation of multidrug ABC transporter gene during cold temperature was reported for psychrophilic gram-negative bacteria Flavobacterium psychrophilum [45]. Similarly, upregulation of a MFS transporter gene during cold temperature was seen in psychrophilic fungus Mrakia psychrophila [46].…”
Section: Translation Regulation Through Translation Initiation Factormentioning
confidence: 72%
“…Both ABC and MFS transporters can play a role in stress resistance, especially in antibiotics resistance [44]. However, previous studies related to psychrophilic organisms also support that ABC and MFS transporters play a role in cold adaptation [45,46]. Upregulation of multidrug ABC transporter gene during cold temperature was reported for psychrophilic gram-negative bacteria Flavobacterium psychrophilum [45].…”
Section: Translation Regulation Through Translation Initiation Factormentioning
confidence: 99%